ASSESSING CISANTI LAKE SEDIMENTS AS ENVIRONMENTAL QUALITY INDICATORS IN THE UPSTREAM OF THE CITARUM RIVER - Fitriani, Dini; Agustine, Eleonora; Hajar Kirana, Kartika; Meliani, Tiara Ayu; Rofifah, Sinthia Anis; Chicilia, Novia; Muhammad, Irfan Handi; Rostika Noviyanti, Atiek; Tamuntuan, Gerald Hendrik (Indonesian Physical Review, 2025)
Environmental conditions in aquatic ecosystems could change due to the entry of additional materials, such as heavy metals and magnetic minerals. These materials, referred to as anthropogenic materials, could be derived from human activities. The presence of the materials could affect the magnetic properties and heavy metals content of river water and sediments. We have analyzed magnetic susceptibility and heavy metal concentration in sediments collected from Cisanti Lake. Cisanti Lake is known as â€œzero kilometersâ€ of the Citarum River. Using the level of heavy metals in sediments, we calculated and evaluated pollution indices in the form of Contamination Factor (CF), Geoaccumulation Index (Igeo), and Pollution Load Index (PLI). The results showed that the magnetic susceptibility of sediments (ðœ’ð¿ð¹) was in the range of 317.2 - 2274.9 (Ã— 10-8) m3kg-1, inferring the dominance of ferrimagnetic minerals in sediments. Based on bivariate analysis of ðœ’ð¿ð¹ and the calculated frequency-dependent magnetic susceptibility or cFD (%), domain states of magnetic minerals are clustered at stable single domain (SSD)/multidomain (MD). Pollution indices of CF and Igeo showed that all sample points were contaminated by Cu at a considerable level.Â  Moderate to significant contamination occurred in the studied area according to the PLI analysis. The positive strong correlation between ðœ’ð¿ð¹ and PLI suggests that magnetic susceptibility serves as a proxy indicator of contamination.Â